2020
DOI: 10.1002/cbdv.202000019
|View full text |Cite
|
Sign up to set email alerts
|

Trifolium pratense (Red Clover) Improve SIRT1 Expression and Glycogen Content in High Fat Diet‐Streptozotocin Induced Type 2 Diabetes in Rats

Abstract: Flowering tops of Trifolium pratense L. (Fabaceae) are known for its traditional medicinal values. In present study, our aim was to investigate effect of standardized aqueous extract of flowering tops of Trifolium pratense L. on insulin resistance and SIRT1 expression in type 2 diabetic rats. Type 2 diabetes was induced by feeding high fat diet and administering low dose of streptozotocin. Diabetic animals were treated with standardized aqueous extract at three different doses. Parameters such as blood glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
3
8
0
1
Order By: Relevance
“…Recent studies have found RC to be effective in treating several diseases; for instance, RC is safe clinically and in vitro for premenopausal patients with hormonesensitive breast cancer (38). Furthermore, a study showed that RC extract (250 mg/Kg) has a significant effect in a rat model of type 2 diabetes (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found RC to be effective in treating several diseases; for instance, RC is safe clinically and in vitro for premenopausal patients with hormonesensitive breast cancer (38). Furthermore, a study showed that RC extract (250 mg/Kg) has a significant effect in a rat model of type 2 diabetes (39).…”
Section: Discussionmentioning
confidence: 99%
“…Ocimum and Trifolium sp. contain many antioxidant compounds which contribute to their intense antiradical activity [ 43 , 44 ] and could have potential human health benefits [ 21 ]. Due to the strong antioxidant capacity, basil acts as a protector to prevent heart diseases, reduce inflammation, lower the incidence of cancers and diabetes [ 40 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…The antioxidant capacity of the formulated hydrogel is due to the chemical composition of EOT, being rich in phenols, flavonoids, volatile oils, etc. [5,25,39].…”
Section: Discussionmentioning
confidence: 99%